PharmPathFinder: a cost-effective and scalable solution to improve pharmacy students' career readiness - Mohd Radzi, Nur Fathiah; Zulkifli, Nur Wahida; Hamdan, Nor Elyzatul Akma; Jamal, Janattul Ain; Nik Mustaffa Shapri, Nik Aisyah Najwa; Abd Wahab, Mohd Shahezwan; Daud @ Ibrahim, Nurulfalahin (Faculty of Pharmacy, 2025)
Pharmacy students often struggle with fragmented learning about pharmacy professions due to the absence of a dedicated course. A survey at UiTM Malaysia revealed that 30% of students had only moderate or lower understanding, while 48% felt unprepared for their careers. A previous one-day program aimed at addressing this gap was costly and labour-intensive. To provide a more efficient solution, we developed PharmPathFinder, using the Plan, Do, Check, and Action (PDCA) tool with 21 steps. This mixed-method study incorporated surveys from alumni and students across four universities, alongside focus group discussions to refine the platform. After launching PharmPathFinder via TikTok, WhatsApp, and Facebook, 98.2% (275 students) expressed satisfaction, citing its usefulness and ease of use. Compared to the previous program, it reduced costs by 73%, time by 77%, and manpower by 75%. PharmPathFinder provides structured insights into four pharmacy specialisations and is accessible to students from their first year, regardless of location. Additionally, it is being promoted in secondary schools to introduce younger students to pharmacy careers.